Shortage of Rabbits or Insufficient Traps? Table-Turning and the Discovery of a PK Gifted Person in Argentina - Gimeno, Juan (Journal of Scientific Exploration, 2015)
<!–[if gte mso 9]> 14.00 <![endif]–> The formation of a sitter-group in Buenos Aires is described. Fifteen weekly meetings were conducted, between April and July 2013, attended by 5 to 9 people each. Ostensible movements of a table were reported. In the last meeting one psychokinetically gifted member was identified. He had witnessed RSPK at home, when aged 11. After identifying him, another 10 meetings were conducted with the only this gentleman present. In these meetings he made a table raise a leg at will, even with the additional weight added to the table. All the meetings were conducted with normal illumination, most of them recorded in video. It was impossible to reproduce most of the table movements by normal means. He was not able to achieve the total levitation of the table, nor any movements without hand contact. Gifted people with remarkable psi abilities are scarce, and in the field of physical phenomena objective investigations of macro-PK seem to be stagnant, or at least without the possibility of publishing encouraging results. The Scole Group investigators (Keen, Ellison & Fontana, 1999), did not employ adequate controls in order to confirm or deny the phenomena demonstrated in darkness. The investigation of the Felix group by Stephen Braude (2014) and others (Michael Nahm (2014) has been deterred by accusations of fraud by its "medium," Kai Mügge. <!–[if gte mso 9]> Normal 0 false false false ES-AR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>